2018
DOI: 10.3390/molecules23010123
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Evaluation of the Biological Properties of the Essential Oil of the Dietary Phytochemical Lippia citriodora

Abstract: The aim of the study was to characterize the chemical composition and biological properties of the essential oil from the plant Lippia citriodora grown in Greece. The essential oil volatiles were analyzed by gas chromatography–mass spectrometry GC-MS indicating citral as the major component. Τhe antimicrobial properties were assayed using the disk diffusion method and the minimum inhibitory and non-inhibitory concentration values were determined. Listeria monocytogenes, Staphylococcus epidermidis, Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Geranial, nerol and benzenamine were not detected in the present study but the others with different values were recognized. Fitsiou et al (2018) revealed that geranial (26.4%), neral (17.2%), nerol (8.0%), geraniol (5.7%), spathulenol (3.3%), 1.8cineol (3.2%) and limonene (2.2%) had high amount in the essential oil of L. citriodora from Greece. Geranial, geraniol and nerol were not found in the essential oil of present study while neral, spathulenol and 1.8-cineol with different percentages were detected in both tested oils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geranial, nerol and benzenamine were not detected in the present study but the others with different values were recognized. Fitsiou et al (2018) revealed that geranial (26.4%), neral (17.2%), nerol (8.0%), geraniol (5.7%), spathulenol (3.3%), 1.8cineol (3.2%) and limonene (2.2%) had high amount in the essential oil of L. citriodora from Greece. Geranial, geraniol and nerol were not found in the essential oil of present study while neral, spathulenol and 1.8-cineol with different percentages were detected in both tested oils.…”
Section: Resultsmentioning
confidence: 99%
“…Lemon verbena [Lippia citriodora Kunth (Verbenaceae)], is one of the most cultivated medicinal plants, which used in the preparation of herbal tea for its lemon-like aroma (Argyropouloua et al, 2007, Kizil et al, 2018. Along with diuretic, antipyretic, antispasmodic, and sedative properties, the antimicrobial and antioxidant effects of this GRAS (Generally Regarded As Safe) listed plant was also demonstrated (Gomes et al, 2006, Farahmandfar et al, 2018, Fitsiou et al, 2018. Therefore, the aim of present study was to describe the chemical profile of two Iranian L. citriodora essential oils and assess their fumigant toxicity against R. dominica and T. castaneum.…”
Section: Introductionmentioning
confidence: 99%
“…Single cell gel electrophoresis (comet) assay was performed as described previously [ 28 , 29 ]. Briefly, HaCaT cells (2 × 10 4 ) were treated with S. raeseri subsp.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a solution of DPPH in ethanol was prepared and this solution (100.0 μL) was added to 100.0 μL of essential oil solutions at different concentrations. The mixture was shaken and left to stand for 30 min in the dark at room temperature, and then we measured the absorbance at 517 nm [ 47 ].…”
Section: Methodsmentioning
confidence: 99%